Towards Resiliency Enhancement of Network of Grid-Forming and Grid-Following Inverters - Silvanus D'silva (19273852) (2023)
This article proposes an autonomous control scheme to mitigate voltage–frequency excursions observed in a network of grid-forming (GFM) and grid-following (GFL) inverters in a power-electronics-dominated grid (PEDG). The proposed control scheme leverages the GFL inverter's ability to dynamically adjust their power set-points as well as change their operation mode on-the-fly to enhance the PEDG resiliency. A supervisory controller comprising of a droop-Δ P estimator coupled with an optimal power allocator module dynamically adjusts the power injections from GFL inverters to maintain the power balance and restore frequency in response to disturbances. Moreover, the proposed self-ranking-based coordinated mode selection algorithm dynamically reconfigures the inverter's operation mode (either GFM or GFL) to enhance the PEDG resiliency in response to events and ensure GFM inverter allocation in grid clusters. Several case studies are performed to validate the feasibility, performance, and robustness of the proposed autonomous control. Finally, the proposed scheme is experimentally validated on a small-scale hardware testbed. Other Information Published in: IEEE Transactions on Industrial Electronics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/tie.2023.3262866